Llama 2: Open Foundation and Fine-Tuned Chat Models - Touvron, Hugo; Martin, Louis; Stone, Kevin; Albert, Peter; Almahairi, Amjad; Babaei, Yasmine; Bashlykov, Nikolay; Batra, Soumya; Bhargava, Prajjwal; Bhosale, Shruti; Bikel, Dan; Blecher, Lukas; et al. (2023)
In this work, we develop and release Llama 2, a collection of pretrained and fine-tuned large language models (LLMs) ranging in scale from 7 billion to 70 billion parameters. Our fine-tuned LLMs, called Llama 2-Chat, are optimized for dialogue use cases. Our models outperform open-source chat models on most benchmarks we tested, and based on our human evaluations for helpfulness and safety, may be a suitable substitute for closed-source models. We provide a detailed description of our approach to fine-tuning and safety improvements of Llama 2-Chat in order to enable the community to build on our work and contribute to the responsible development of LLMs.
tex.ids= touvronLlama2Open2023 arXiv: 2307.09288 [cs] <标题>: Llama 2：开放基础模型与精调聊天模型 Read_Status: New Read_Status_Date: 2026-01-26T11:32:33.304Z
Keywords: /unread; Computer Science - Artificial Intelligence; Computer Science - Computation and Language